2023
DOI: 10.4274/ejbh.galenos.2023.2023-6-5
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Psychological Resilience in the Relationship Between Spiritual Well-Being and Supportive Care Needs in Women With Breast Cancer

Özlem Soyer Er,
Hamide Nur Erkan

Abstract: Psychological resilience contributes to the reduction of supportive care needs of breast cancer patients by affecting spiritual well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Patients are particularly more severe if they have advanced breast cancer [ 6 ]. Therefore, spiritual care is necessary for patients with advanced breast cancer for them to overcome pain; appreciate the value of life; and find spiritual sustenance, gain hope, love, forgiveness, and strength, that is spiritual care needs [ 7 , 8 ]. Furthermore, several research studies have demonstrated the potential benefits of spirituality in cancer coping strategies, diagnosis, treatment, and rehabilitation for patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Patients are particularly more severe if they have advanced breast cancer [ 6 ]. Therefore, spiritual care is necessary for patients with advanced breast cancer for them to overcome pain; appreciate the value of life; and find spiritual sustenance, gain hope, love, forgiveness, and strength, that is spiritual care needs [ 7 , 8 ]. Furthermore, several research studies have demonstrated the potential benefits of spirituality in cancer coping strategies, diagnosis, treatment, and rehabilitation for patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%